Patient-Reported Outcome Measures in Neurosurgery: A Review of the Current Literature. Issue 4 (18th November 2017) - Ghimire, Prajwal; Hasegawa, Harutomo; Kalyal, Nida; Hurwitz, Victoria; Ashkan, Keyoumars
Abstract: BACKGROUND: Patient-reported outcome measures (PROMs) play an important role in the evaluation of health outcomes, quality of life, and satisfaction, and have been successfully utilized in many areas of clinical medicine and surgical practice. The prevalence of PROMs in neurosurgery is not known. OBJECTIVE: To review the PROMs that have been utilized in the published neurosurgery literature to date. METHODS: Articles were searched in MEDLINE, EMBASE, HMIC Health Management Information Consortium, PsycARTICLES, and PsycINFO using search terms related to neurosurgery and PROMs, published from 1806 to August 2016. A total of 268 articles were identified that were stratified by the inclusion and exclusion criteria leading to a total of 137 articles. Twenty-six PROMs, involving both adult and pediatric populations, were identified. RESULTS: A large number of generic and disease-specific PROMs are used in the neurosurgical literature. Generic PROMs are usually nonspecific measures of health status. Disease-specific PROMs may not address issues relevant to neurosurgical procedures. There are very few neurosurgery-specific PROMs that take into account the impact of a neurosurgical procedure on a specific condition. CONCLUSION: PROMs that currently feature in the neurosurgical literature may not address the specific outcomes relevant to neurosurgical practice. There is an emergent need for generic and disease-specific PROMs to be validated in neurosurgical patients and neurosurgery-specific PROMs developed to address unmet needs of patients undergoing neurosurgical procedures.